The perceptions of African refugee background students : their schooling in WA and their adjustment to the Australian cultural context - Mbano, Noah T. (Curtin University, 2012)
This study reports on an investigation into the perceptions of African Refugee Background students about their schooling in WA and their adjustment to the Australian cultural context. The recent cohort of African refugee children and young adolescents arriving in WA schools presents unique challenges to teachers because many of these refugees have a history of trauma, multiple displacements, extended stays in refugee camps and severely disrupted schooling. There is clearly a need for further studies into the settlement of this vulnerable group in WA.The present study is a perception study based on a qualitative approach. In total 180 participants were involved. Data was collected by way of focus group discussions and individual interviews. Classroom observations were also undertaken. The data was analysed thematically, and in addition case studies were developed to illustrate the evidence that emerged.The findings show that participants are generally happy and have settled well in Australia. However, they do have concerns related to the issues of culture and acculturation, their transition into Australian classrooms, and their social and self-identity. In fact, some African Refugee Background students are experiencing an identity crisis as a result of their migration to Australia. Despite this, many are highly motivated to learn English, to achieve their academic, social and long term goals and to integrate into the Australian community. Together these factors have important implications for pedagogy.While the current study has gone some way towards highlighting issues that are impacting on African Refugee Background students, there is still a need for further research to explore ways to assist African Refugee Background students to deal with the demands of their new context in WA.